Pembinaan Pengendalian Terpadu Penyakit Tanaman Padi di Kelompok Tani Desa Sumber Agung, Metro Kibang, Lampung Timur - Krisnarini, Krisnarini; Yatmin, Yatmin (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The farmer group in Sumber Agung Village is a farmer group involved in cultivating rice as a leading commodity in Metro Kibang District, East Lampung Regency. Rice plant diseases are a limiting factor in rice cultivation activities in Sumber Agung Village. Several rice diseases that are problems in Sumber Agung Village are blast disease, tungro disease, and bacterial leaf blight disease. The limited knowledge of farmers in recognizing various diseases in rice plants as well as effective and efficient control measures are the main problems that have not been able to be overcome by farmer groups in Sumber Agung Village. The aim of this community service activity is to transfer knowledge from universities (service teams) to the community by socializing rice diseases and environmental management (selection of varieties, use of quality seeds, regulation of plant irrigation, and simultaneous planting by applying appropriate cultivation techniques) as integrated disease control strategy in rice plants. Based on the activities that have been carried out, members of the Farmers Group feel that the service activities carried out are very beneficial for farmers because these activities provide knowledge and insight for farmers in the context of controlling diseases in rice plants. This can also be seen from the participants who are very enthusiastic about participating in the activities shown by his activeness in listening and responding to the delivery of material as well as actively asking questions and responding to every problem discussed.